2008
DOI: 10.1192/bjp.bp.106.032102
|View full text |Cite
|
Sign up to set email alerts
|

Semantic priming in schizophrenia: Systematic review and meta-analysis

Abstract: Meta-analysis provides qualified support for increased semantic priming as a psychological abnormality underlying thought disorder. However, the possibility that the effect is an artefact of general slowing of reaction time in schizophrenia has not been excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
92
1
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(109 citation statements)
references
References 45 publications
10
92
1
6
Order By: Relevance
“…However, the underlying mechanisms of this remain unclear. One popular theory is disruption in the semantic memory system, resulting in overinclusive thinking (Cameron, 1939;Payne, 1960;Chen et al, 1994), differences in the spreading of activation through the network (Maher, 1983;Moritz et al, 2002; for a meta analysis see Pomarol-Clotet et al, 2008), a disorganization within the semantic system (Paulsen et al, 1996), or a disruption of expression at the semantic level (McKenna and Oh, 2005),. However, studies adopting alternative methodological frameworks (i.e., not priming paradigms) and different statistical approaches have not found support for notions of a difference in the putative boundaries of categories (Elvevåg et al, 2002), or underlying semantic structure and organization (Elvevåg and Storms, 2003;Cohen et al, 2005;Elvevåg et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, the underlying mechanisms of this remain unclear. One popular theory is disruption in the semantic memory system, resulting in overinclusive thinking (Cameron, 1939;Payne, 1960;Chen et al, 1994), differences in the spreading of activation through the network (Maher, 1983;Moritz et al, 2002; for a meta analysis see Pomarol-Clotet et al, 2008), a disorganization within the semantic system (Paulsen et al, 1996), or a disruption of expression at the semantic level (McKenna and Oh, 2005),. However, studies adopting alternative methodological frameworks (i.e., not priming paradigms) and different statistical approaches have not found support for notions of a difference in the putative boundaries of categories (Elvevåg et al, 2002), or underlying semantic structure and organization (Elvevåg and Storms, 2003;Cohen et al, 2005;Elvevåg et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…21 Based on these observations, it has been suggested that automatic spreading of lexical activation is accelerated and/or travels abnormally large distances in thoughtdisordered patients with schizophrenia. 18,22 In line with this assumption, a functional neuroimaging study reported increased activity during indirect automatic priming in patients with schizophrenia compared with controls in regions associated with semantic processing. 23 This excessive spread of activation has been hypothesized to constitute the cognitive correlate of positive formal thought disorder.…”
Section: Introductionmentioning
confidence: 64%
“…23 This excessive spread of activation has been hypothesized to constitute the cognitive correlate of positive formal thought disorder. 9,18,21 However, it is not clear how these findings relate to the dopaminergic dysfunction assumed to underlie schizophrenia. 24,25 Several studies showing a reduction of indirect semantic priming upon administration of levodopa (L-Dopa) or dopaminergic agonists in healthy individuals [26][27][28] have led to the suggestion that dopamine (DA) increases the signalto-noise ratio within the semantic network, resulting in a more focused activation pattern.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Word completion tasks are widely used to study different aspects of implicit memory in clinical and non-clinical populations (Geraci & Hamilton, 2009;Marques, Spataro, Cestari, Sciarretta, & Rossi-Arnaud, 2016;Mitchell & Bruss, 2003;Millet, Le Goff, Bouisson, Dartigues, & Amieva, 2010;Pomarol-Clotet, Oh, Laws, & McKenna, 2008). In these studies implicit memory has been evaluated through repetition priming, usually defined as the benefit in the processing of a stimulus when it has been recently processed (Roediger & Blaxton, 1987).…”
mentioning
confidence: 99%